Realitas dan Viralitas: Dinamika dan Isu dalam Era Media Baru di Indonesia - Purba, Herman; Rinaldo, Edo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
The reality of society in new media today is very depend on user-generated content. A qualitative approach and the literature review method were used in this study, which aims to provide an in-depth description of the dynamics and issues related to reality and virality that are developing in Indonesian society as current users of new media. The results of this study indicate that the presence of algorithms and features in new media allows information and content generated by users to be used quickly and become a topic of conversation with other users. Virality and reality in social life can be seen by the presence of the infodemic during the COVID-19 pandemic, its application to digital marketing concepts, and shaping the image and identity of each individual on social media. Apart from that, this phenomenon can also be linked to political dynamics in Indonesia which is marked by the presence of buzzers, campaigns in the digital space, and the process of voicing the aspirations of the people to policy makers.